Correlation Of The Role Playing Method With Collaboration Skills In Social Studies Study Groups - Suhendar, Suhendar; Tetep; Eldi Mulyana (SAHUR Journal, 2024)
The background of this research is that social studies learning in schools is also not optimal in implementing and familiarizing the experience of democratic, social life values ​​by involving students and the school community in various class and school activities. The purpose of this study is to identify the implementation of the role playing learning method which is still an obstacle in creating effective learning. This is what still causes learning to not be able to achieve the expected goals. The description above is an illustration of how important it is to create active and fun student learning. The research method used is quantitative method with a type of correlation, data collection techniques through questionnaires, observation, interviews and documentation studies. Data analysis techniques through the normality test, simple linear regression test. The results of this study show that the constant value is 14.663, systematically this constant value states that when the value of role playing is 0, cooperation skills have a value of 14.663. While the regression coefficient line is 0.748, the positive value results illustrate that the direction of the relationship between the role playing variable and the cooperation skills variable is unidirectional, thus the regression equation can be written Y = 14.663 + 0.748 x. This means that the value of 0.748 is the change in the regression line, where each unit of the value of the X variable will be followed by a change in the Y value of 0.748